FAKTOR-FAKTOR KEJADIAN BERAT BADAN BAYI LAHIR DI RSUD dr. SOEDARSO PONTIANAK - Widiarsih, Fitria; Marlenywati, Marlenywati; Abrori, Abrori (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak, 2015)
Birth weight is the weight of neonates at birth weighed within an hour or shortly after the birth. Body weight is used to diagnose whether the baby's weight is normal or low (LBW).This study aimed to discover the factors related to height, body weight gain, upper arm circumference, hemoglobin level, maternal age, eating abstinence, carbonated beverages intake, and the incidence of newborn infants birth weight at Delivery Room of RSUD dr. Soedarso Pontianak.A cross sectional design was carried out in this study. The samples were 93 respondents who were selected by using accidental sampling technique. The data were analyzed by employing chi square test.The study revealed two findings. First, there were correlation of birth weight gain (p value=0,000), hemoglobin level (p value=0,017), upper arm circumference (p value=0,001), maternal age (p value=0,018), eating abstinence (p value=0,047), and the incidence of newborn infants birth weight. second, there were no correlation of height (p value=0,142), carbonated beverages intake, and the incidence of newborn infants birth weightFrom the findings, the management of Soedarso hospital should provide family planning counseling, particularly on the importance setting the age for pregnancy, pregnancy spacing, and antenatal care, particularly for those who are at risk of pregnancy.Key words: body weight gain, hemoglobin level, upper arm circumference, maternal age, eating abstinence